International Conference on Advanced Computing Networking and Informatics ICANI-2018 - Kamal, Raj; Henshaw, Michael; Nair, Pramod S. (Advances in Intelligent Systems and Computing, 2019)
The book comprises selected papers presented at the International Conference on Advanced Computing, Networking and Informatics (ICANI 2018), organized by Medi-Caps University, India. It includes novel and original research work on advanced computing, networking and informatics, and discusses a wide variety of industrial, engineering and scientific applications of the emerging techniques in the field of computing and networking.